Risk of Severe Adverse Maternal and Neonatal Outcomes in Deliveries with Repeated and Primary Cesarean Deliveries versus Vaginal Deliveries: A Cross-Sectional Study - Kiattisak Kongwattanakul; Rungroj Thamprayoch; Chumnan Kietpeerakool; Pisake Lumbiganon (Hindawi Limited, 2020)
Objective. To determine risks of severe adverse maternal and neonatal outcomes in women with repeated cesarean delivery (CD) and primary CD compared with those with vaginal delivery (VD). Methods. Data of this cross-sectional study were extracted from 2,262 pregnant women who gave birth between August 2014 and December 2016, at Srinagarind Hospital, Khon Kaen University. Severe maternal outcomes were categorized based on the World Health Organization criteria. Adjusted odds ratio (aOR) and 95% confidence intervals (CI) were calculated to indicate the risk of severe adverse maternal and neonatal outcomes among women underwent CD compared with those who underwent VD. Results. There were no cases of maternal death in this study. CD significantly increased risk of severe adverse maternal outcomes (SMO) (aOR 10.59; 95% CI, 1.19-94.54 for primary CD and aOR 17.21; 95% CI, 1.97-150.51 for repeated CD) compared with women who delivered vaginally. When compared with vaginal delivery, the risks of neonatal near miss (NNM) and severe adverse neonatal outcomes (SNO) were significantly higher in primary CD group (aOR 1.71; 95% CI 1.17-2.51 and aOR 1.66; 95% CI 1.14-2.43), respectively. For repeated CD, the risks were borderline significant (aOR, 1.58; 95% CI, 0.98-2.56 for NNM and aOR, 1.61; 95% CI, 0.99-2.60 for SNO). Conclusion. Primary and repeated CD significantly increased the risk of SMO compared with VD. Risks of NNM and SNO were also significantly increased in women with primary CD. The risks of NNM and SNO for repeated CD trended toward a significant increase.